Metal-doped biphase nickel sulfide electrocatalyst and preparation method and application thereof

The iron-doped dual-phase nickel sulfide electrocatalyst solves the stability problem of the existing OER reaction electrocatalyst in an alkaline environment and the scarcity of precious metal resources, achieves an efficient and stable water electrolysis hydrogen production reaction, and reduces the cost Preparation costs.

CN119332294APending Publication Date: 2025-01-21YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411778395.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, OER reaction electrocatalysts such as IrO2 and RuO2 used to electrolyze hydrogen production in water have insufficient catalytic stability in alkaline electrolyte solutions, and precious metal resources are scarce, making it difficult to meet large-scale industrial needs.

Method used

An iron-doped biphasic nickel sulfide (Fe-NiS/NiS2) electrocatalyst is used, prepared by a hydrothermal reaction method, using thioacetamide and triethylenetetramine as sulfur sources and complexing agents, and adjusting reaction conditions to improve the catalyst OER reactivity.

Benefits of technology

Significantly improves the activity of nickel sulfide electrocatalytic OER reaction, reduces preparation costs, provides more stable catalytic performance, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332294A_ABST
    Figure CN119332294A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-doped dual-phase nickel sulfide electrocatalyst and a preparation method and application thereof, the metal doped in the catalyst is iron, the dual-phase nickel sulfide is NiS and NiS2, and the chemical formula is Fe-NiS / NiS2; the preparation method comprises the following steps: (1) dissolving thioacetamide, nickel salt and iron salt in water, uniformly mixing, adding triethylene tetramine, and uniformly mixing to obtain a mixed solution; and (2) carrying out a hydrothermal reaction on the mixed solution, and after the reaction is finished, washing and drying the precipitate to obtain the iron-doped biphase nickel sulfide electrocatalyst. In the catalyst, more electro-catalytic reaction sites are provided by effective doping of the Fe element and generation of the two-phase nickel sulfide, so that the activity of nickel sulfide electro-catalytic OER reaction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalyst hydrogen production, and in particular relates to a metal-doped dual-phase nickel sulfide electrocatalyst and a preparation method and application thereof. Background Art

[0002] With the gradual consumption of fossil energy and the increasing severity of environmental problems, exploring clean energy alternatives to fossil fuels is a global issue that needs to be addressed. Hydrogen, as a renewable clean energy source, stands out among fossil fuels. Hydrogen production by water electrolysis is considered to be one of the most effective ways to convert electrical energy into chemical energy. The hydrogen production reaction by water electrolysis involves the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Since the oxygen evolution reaction involves a four-electron transfer process, it has a high reaction energy barrier, which limits the conversion efficiency of water electrolysis and is a bottleneck problem in the production process. So far, the most effective OER reaction electrocatalysts such as IrO2 and RuO2 have excellent electrocatalytic activity and stability, but their catalytic stability in alkaline electrolyte solutions is still unsatisfactory, which to some extent restricts their application areas. More importantly, precious metal material resources are scarce and expensive, making it difficult to meet large-scale industrial needs. Therefore, the development of cheap, efficient and stable OER reaction electrocatalysts is a scientific problem that needs to be solved urgently.

[0003] As a non-precious metal catalyst with electrocatalytic OER reaction activity, nickel sulfide has attracted much attention. The unique eight electrons in nickel 3d orbital facilitate the simple adjustment of the catalyst electronic structure, thus helping to improve the electrocatalytic OER reaction activity. However, the electrocatalytic OER reaction activity of single nickel sulfide in the existing technology needs to be improved. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a metal-doped dual-phase nickel sulfide electrocatalyst for improving the electrocatalytic OER activity of nickel sulfide; the second purpose of the present invention is to provide a method for preparing the metal-doped dual-phase nickel sulfide electrocatalyst; the third purpose of the present invention is to provide an application of the metal-doped dual-phase nickel sulfide electrocatalyst.

[0005] Technical solution: The metal-doped dual-phase nickel sulfide electrocatalyst described in the present invention comprises iron as the doped metal, NiS and NiS2 as the dual-phase nickel sulfide, and its chemical formula is Fe-NiS / NiS2.

[0006] Iron is the most abundant transition metal element with very low cost. Appropriate amount of iron doping can also effectively adjust the electronic structure of nickel sulfide electrocatalysts and increase the active sites of electrochemical reactions, thereby further improving the OER reaction activity of nickel sulfide electrocatalysts.

[0007] Preferably, the molar ratio of iron to nickel is 1:2 to 9. Compared with the nickel sulfide catalyst without iron doping, the catalytic performance is improved with the addition of iron, the catalytic performance is optimal when the iron-nickel ratio is 1:4, and the catalytic performance begins to decline with a higher ratio of iron doping, indicating that an appropriate amount of iron doping is beneficial to improving the OER catalytic performance of nickel sulfide electrocatalytic materials.

[0008] More preferably, the molar ratio of iron to nickel is 1:2-4.

[0009] The method for preparing the metal-doped dual-phase nickel sulfide electrocatalyst of the present invention comprises the following steps:

[0010] (1) dissolving thioacetamide (TAA), nickel salt, and iron salt in water, mixing them evenly, and then adding triethylenetetramine (TETA), mixing them evenly to obtain a mixed solution;

[0011] (2) subjecting the mixed solution to a hydrothermal reaction, and after the reaction is completed, washing and drying the precipitate to obtain the iron-doped dual-phase nickel sulfide electrocatalyst.

[0012] Thioacetamide is an important precursor for preparing sulfur-containing materials. In the hydrothermal reaction, it can release sulfur by thermal decomposition, providing an effective sulfur source for the synthesis of catalysts. The sulfur material obtained by using thioacetamide as a sulfur source has abundant sulfur defects and unsaturated surfaces, which increases the surface active sites of the catalyst, thus showing excellent electrocatalytic performance. At the same time, it can adjust the environmental conditions of the hydrothermal reaction, inhibit undesirable side reactions, and improve the selectivity of the target product.

[0013] As a solvent and complexing agent, triethylenetetramine can effectively dissolve precursor materials, provide a good reaction environment for the synthesis of electrocatalysts, and help improve the synthesis efficiency of catalysts during hydrothermal synthesis under high temperature and high pressure conditions. Its polarity and hydrogen bonding ability can form complexes with metal ions, improve the dispersion of metal precursors in the solution, and prevent metal aggregation or precipitation. It helps to obtain a more uniform metal distribution during the synthesis process and improve the activity of the catalyst. At the same time, triethylenetetramine has a weak alkalinity, which can adjust the pH value in the reaction system, helping to affect the morphology, crystal structure and catalytic performance of the material.

[0014] Under the high temperature and high pressure of the hydrothermal reaction, thioacetamide provides a sulfur source for the synthesis of the catalyst through thermal decomposition. TETA and deionized water are mixed as a solvent and a complexing agent to evenly distribute the iron and nickel ions in the solution. At the same time, the reaction environment is adjusted so that the iron source and the nickel source coexist in the reaction solution. As the temperature and pressure change, the iron ions gradually replace part of the nickel position to form a doped nickel sulfide structure, and finally a solid precipitate product is obtained.

[0015] Preferably, the temperature of the hydrothermal reaction is 140-200° C., and the reaction time is 10-25 h.

[0016] Preferably, the nickel salt is nickel chloride hexahydrate (NiCl2·6H2O).

[0017] Preferably, the iron salt is ferrous ammonium sulfate Fe(NH4)2(SO4)2·6H2O.

[0018] Preferably, the drying condition is: drying at 50-80° C. for 6-12 hours.

[0019] Preferably, the washing is performed by washing with deionized water and anhydrous ethanol in sequence.

[0020] The invention relates to the use of the metal-doped dual-phase nickel sulfide electrocatalyst in the production of hydrogen by electrolysis of water.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The dual-phase structure of NiS (12-0041) and NiS2 (11-0099), the effective doping of Fe element and the formation of dual-phase nickel sulfide provide more electrocatalytic reaction sites, thereby improving the activity of nickel sulfide electrocatalytic OER reaction; (2) The one-step hydrothermal method is adopted, the preparation method is simple and effective, the preparation cost is low, and the design is reasonable. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the XRD pattern of the electrocatalyst sample of Example 1;

[0023] Figure 2 (a) TEM image of the electrocatalyst of Example 1; (b-c) HRTEM images of the electrocatalyst of Example 1; (d-f) element distribution images of the electrocatalyst of Example 1;

[0024] Figure 3 is the XRD pattern of the electrocatalyst sample of Comparative Example 1;

[0025] Figure 4 is the XRD pattern of the electrocatalyst sample of Comparative Example 2;

[0026] Figure 5 is the XRD pattern of the electrocatalyst sample of Comparative Example 3;

[0027] Figure 6 The LSV polarization curves of the catalyst samples of Example 1 and Comparative Examples 1 to 3 are shown;

[0028] Figure 7 LSV polarization curves of the catalyst samples of Examples 1 to 3;

[0029] Figure 8It is the Tafel slope diagram of Example 1, Comparative Example 1 and Comparative Example 2;

[0030] Fig. 9 The electrochemical capacitance (C dl )picture;

[0031] Fig.10 The impedance diagrams of the samples of Example 1, Comparative Example 1 and Comparative Example 2 are shown;

[0032] Fig.11 This is the stability diagram of the electrocatalyst sample in Example 1. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below in conjunction with embodiments.

[0034] Example 1

[0035] The metal-doped dual-phase nickel sulfide electrocatalyst of the present invention has a molar ratio of Fe:Ni=2:8 and a volume ratio of TETA:H2O=1:2. The preparation method thereof comprises the following steps:

[0036] (1) At room temperature, weigh 2 mmol (0.1502 g) of thioacetamide, 1.6 mmol (0.3803 g) of nickel chloride hexahydrate, and 0.4 mmol (0.1568 g) of ammonium ferrous sulfate, dissolve them in 16 ml of deionized water in sequence, stir them magnetically for 30 min, then add 8 ml of triethylenetetramine (TETA) (pH = 8) to the stirred mixed solution, and continue stirring for 30 min;

[0037] (2) The obtained mixed solution was placed in a polytetrafluoroethylene reactor (50 ml) and heated in a drying oven at 180° C. for 20 h. The obtained precipitate (obtained after the reactor was naturally cooled) was washed three times with deionized water and anhydrous ethanol respectively, and the obtained precipitate was dried at 60° C. for 8 h to obtain the iron metal-doped dual-phase nickel sulfide electrocatalyst.

[0038] Example 2

[0039] The metal-doped dual-phase nickel sulfide electrocatalyst of the present invention has a molar ratio of Fe:Ni=1:9 and a volume ratio of TETA:H2O=1:2, and the preparation method thereof comprises the following steps:

[0040] (1) At room temperature, weigh 2 mmol (0.1502 g) of thioacetamide, 1.8 mmol (0.4278 g) of nickel chloride hexahydrate, and 0.2 mmol (0.0784 g) of ammonium ferrous sulfate, dissolve them in 16 ml of deionized water in sequence, stir them magnetically for 30 min, then add 8 ml of triethylenetetramine (TETA) (PH = 8) to the stirred mixed solution, and continue stirring for 30 min;

[0041] (2) The obtained mixed solution was placed in a polytetrafluoroethylene reactor (50 ml) and heated in a drying oven at 180° C. for 20 h. The obtained precipitate (obtained after the reactor was naturally cooled) was washed three times with deionized water and anhydrous ethanol respectively, and the obtained precipitate was dried at 60° C. for 8 h to obtain the iron metal-doped dual-phase nickel sulfide electrocatalyst.

[0042] Example 3

[0043] The metal-doped dual-phase nickel sulfide electrocatalyst of the present invention has a molar ratio of Fe:Ni=3:7 and a volume ratio of TETA:H2O=1:2. The preparation method thereof comprises the following steps:

[0044] (1) At room temperature, 2 mmol (0.1502 g) of thioacetamide, 1.4 mmol (0.3327 g) of nickel chloride hexahydrate, and 0.6 mmol (0.2352 g) of ammonium ferrous sulfate were weighed and dissolved in 16 ml of deionized water in sequence, and magnetically stirred for 30 min. Then, 8 ml of triethylenetetramine (TETA) (pH = 8) was added to the stirred mixed solution, and stirring was continued for 30 min.

[0045] (2) The obtained mixed solution was placed in a polytetrafluoroethylene reactor (50 ml) and heated in a drying oven at 180° C. for 20 h. The obtained precipitate (obtained after the reactor was naturally cooled) was washed three times with deionized water and anhydrous ethanol respectively, and the obtained precipitate was dried at 60° C. for 8 h to obtain the iron metal-doped dual-phase nickel sulfide electrocatalyst.

[0046] Comparative Example 1

[0047] On the basis of Example 1, no ammonium ferrous sulfate was added, and other conditions remained unchanged.

[0048] Comparative Example 2

[0049] On the basis of Example 1, TETA was not added and other conditions remained unchanged.

[0050] Comparative Example 3

[0051] On the basis of Example 1, 8 ml of potassium hydroxide solution with a pH of 8 was used instead of TETA, and the other conditions remained unchanged.

[0052] Structural characterization

[0053] The structures of the iron-doped dual-phase nickel sulfide catalyst prepared in Example 1 and the catalysts prepared in Comparative Examples 1 to 3 were characterized. Figures 1 to 5 shown.

[0054] Figure 1 This is the XRD spectrum of the iron-doped dual-phase nickel sulfide electrocatalyst sample prepared in Example 1. Analysis shows that a sample with a dual-phase nickel sulfide structure is successfully prepared (JCPDS card numbers: 12-0041 and 11-0099).

[0055] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the iron-doped dual-phase nickel sulfide electrocatalyst sample prepared in Example 1. It was observed that the sample exhibited a typical nanosheet structure; (b~c) The lattice fringe spacings of 0.481nm and 0.189nm correspond to the NiS(110) crystal plane and NiS2(220) crystal plane, respectively; (d~f) are element distribution diagrams of the electrocatalyst in Example 1. It can be seen that the three elements S, Fe and Ni are uniformly distributed in the entire catalyst sample.

[0056] Figure 3 This is the XRD spectrum of the electrocatalyst sample of Comparative Example 1, which is a single NiS phase (JCPDS card number: 12-0041).

[0057] Figure 4 The XRD spectrum of the electrocatalyst sample of Comparative Example 2 shows that the phases are NiS, Ni3S4 and Ni 0.96 S three mixture phases (JCPDS card numbers: 12-0041, 43-1469, 50-1791).

[0058] Figure 5 This is the XRD spectrum of the electrocatalyst sample of Comparative Example 3, and the physical phase is a mixture of NiS and Ni3S4 (JCPDS card number: 12-0041, 43-1469).

[0059] Performance Characterization

[0060] (1) OER electrocatalytic activity test of samples

[0061] Test method: The OER performance of the samples was tested in 1.0 M KOH solution using the traditional three-electrode method. The three groups of samples were tested at a current density of 10 mA / cm using linear sweep voltammetry (LSV). 2 The corresponding overpotential. The test results are as follows Figures 6 to 11 shown.

[0062] Figure 6The OER electrocatalytic activity comparison test diagram of the samples obtained in Example 1 (Fe:Ni=1:4, TETA:8ml, denoted as Example 1), Comparative Example 1 (Fe:Ni=0:1), Comparative Example 2 (Fe:Ni=1:4), and Comparative Example 3 (Fe:Ni=1:4, 8ml potassium hydroxide solution with a pH of 8). Figure 3 It can be obtained that the overpotential of Example 1 is 268 mV, which is lower than the overpotential of Comparative Example 1 (375 mV), the overpotential of Comparative Example 2 (343 mV), and the overpotential of Comparative Example 3 (322 mV).

[0063] The overpotential of Comparative Example 1 is higher than that of Example 1 because Comparative Example 1 is not doped with iron. Without doping, the obtained catalyst has only a single NiS phase. The material with a single phase may require higher energy to carry out the OER reaction, and the catalytic performance is not as good as the dual-phase nickel sulfide (NiS and NiS2) of Example 1. The interaction between different phases in Example 1 may promote the catalytic mechanism of OER, change the generation and conversion path of the intermediate species of the reaction, and thus obtain higher catalytic activity.

[0064] The overpotential of Comparative Example 2 is higher than that of Example 1 because TETA is not added in Comparative Example 2, and the generated phases are NiS, Ni3S4 and Ni 0.96 S three mixture phases. In contrast, the TETA added in Example 1, as an organic solvent, has a strong coordination ability and a low polarity, and is more likely to promote the interaction between metal ions than water. At the same time, the presence of the organic solvent may enhance the interaction between nickel and sulfur, making the formation of the NiS2 phase more preferential, and the formed NiS2 may have a better nanostructure, achieve uniform phase distribution and particle size, and thus provide better performance in catalysis and other applications. Comparative Example 2 Ni3S4 and Ni generated when water is used as the solvent 0.96 The S phase may not be stable enough under certain conditions, resulting in poor performance.

[0065] The overpotential of Comparative Example 3 is higher than that of Example 1 because TETA is not added in Comparative Example 3, but an inorganic alkaline solvent potassium hydroxide solution with the same pH is used instead. TETA organic solvent has a strong coordination ability and can more effectively form a coordination complex with metal ions (such as iron and nickel), thereby improving the activity and solubility of metal ions, and the doped iron ions are more easily evenly dispersed in the nickel sulfide matrix, thereby enhancing the catalytic performance. In contrast, potassium hydroxide solution is more biased towards the polarity of water, which may cause uneven doping and lead to insufficient activity of catalytic sites.

[0066] Figure 7The OER electrocatalytic activity comparison test diagram of the samples obtained in Example 1, Example 2 (Fe:Ni=1:9, TETA:8ml), and Example 3 (Fe:Ni=3:7, TETA:8ml) shows that at a current density of 10mA / cm 2 The overpotential of Example 1 is 268 mV, which is lower than the overpotential of Example 2 (284 mV) and the overpotential of Example 3 (275 mV). This indicates that an appropriate iron doping ratio within a certain range is beneficial to increasing the electrocatalytic OER reaction performance of nickel sulfide.

[0067] (2) Catalytic kinetics test

[0068] The Tafel slope was obtained by plotting the overpotential versus log(J) of the LSV polarization curves of Example 1, Comparative Example 1 and Comparative Example 2, and the OER kinetics were further evaluated. The results are as follows: Figure 8 shown.

[0069] Example 1 (67.5 mV / dec), Comparative Example 1 (155.9 mV / dec), Comparative Example 2 (119.3 mV / dec), Example 1 has a lower Tafel slope, indicating that Example 1 also improves the kinetics of the OER electrocatalytic process, showing higher OER activity and rapid catalytic kinetics.

[0070] (3) Electrochemical capacitance test

[0071] In order to evaluate the effective electrochemical active area surface area (ECSA) of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2, the electrochemical capacitance (C dl ). According to the formula ECSA=C dl / Cs can be used to know the electrochemical active area (ECSA) of the working electrode and the C dl The value is directly proportional to the test result. Fig. 9 shown.

[0072] Depend on Fig. 9 It can be obtained that the C of the electrode in comparative example 1 is dl The value is 0.164mF / cm 2 , C of the electrode of Comparative Example 2 dl The value is 0.285mF / cm 2 , C of the electrode of Example 1 dl The value is 0.303mF / cm 2 This result indicates that the doping of iron is beneficial to increase the electrochemically active surface area (ECSA), provide more active catalytic sites for OER catalysis, and achieve better catalytic performance.

[0073] (4) Electrochemical impedance spectroscopy

[0074] The initial electrode potential of the test was 0.47 V and the test frequency range was 0.01 to 10 -5 Hz, the test results are as follows Fig.10 shown.

[0075] Fig.10 It is the electrochemical impedance spectra (EIS) of Example 1, Comparative Example 1 and Comparative Example 2. Through the alternating current impedance spectrum (EIS), it can be seen that Example 1 shows the smallest Nyquist semicircle diameter, indicating that the electrode surface charge transfer resistance (Rct) is the smallest, which is also an important reason why the electrode of Example 1 has the relatively best OER electrocatalytic performance.

[0076] (5) Constant current Vt stability test

[0077] At 10mA / cm 2 A 24h constant current Vt test was carried out under the following conditions. The test results are as follows: Fig.11 shown.

[0078] Fig.11 This is a constant current Vt stability test diagram of Example 1. As can be seen from the figure, Example 1 has a constant current Vt stability of 10 mA / cm 2 During the electrolysis process of the 24h constant current Vt test under the same conditions, the current density remained stable with a small fluctuation range, proving that its electrocatalytic reaction has high stability.

Claims

1. A metal-doped dual-phase nickel sulfide electrocatalyst, characterized in that: The doped metal is iron, the dual-phase nickel sulfide is NiS and NiS2, and its chemical formula is Fe-NiS / NiS2.

2. The metal-doped dual-phase nickel sulfide electrocatalyst according to claim 1, characterized in that: The molar ratio of iron to nickel is 1:2-9.

3. The metal-doped dual-phase nickel sulfide electrocatalyst according to claim 1, characterized in that: The molar ratio of iron to nickel is 1:2-4.

4. A method for preparing the metal-doped dual-phase nickel sulfide electrocatalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving thioacetamide, nickel salt and iron salt in water, mixing uniformly, and then adding triethylenetetramine, mixing uniformly to obtain a mixed solution; (2) subjecting the mixed solution to a hydrothermal reaction, and after the reaction is completed, washing and drying the precipitate to obtain the iron-doped dual-phase nickel sulfide electrocatalyst.

5. The method for preparing a metal-doped dual-phase nickel sulfide electrocatalyst according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 140-200°C.

6. The method for preparing a metal-doped dual-phase nickel sulfide electrocatalyst according to claim 4, wherein the nickel salt is nickel chloride hexahydrate.

7. The method for preparing a metal-doped dual-phase nickel sulfide electrocatalyst according to claim 4, wherein the iron salt is ammonium ferrous sulfate.

8. The method for preparing a metal-doped dual-phase nickel sulfide electrocatalyst according to claim 4, wherein the drying condition is: drying at 50-80°C for 6-12 hours.

9. The method for preparing a metal-doped dual-phase nickel sulfide electrocatalyst according to claim 4, wherein the washing is performed by washing with deionized water and anhydrous ethanol in sequence.

10. Use of the metal-doped dual-phase nickel sulfide electrocatalyst according to any one of claims 1 to 3 in hydrogen production by electrolysis of water.